2019
DOI: 10.1292/jvms.18-0309
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological evaluation of cats associated with feline polycystic kidney disease caused by the feline <i>PKD1</i> genetic mutation in Japan

Abstract: Feline polycystic kidney disease (PKD), an inherited autosomal dominant disease, has been reported to occur mostly in Persian or Persian related cats, and to be associated with a mutation from C to A at position 10063 in exon 29 of the feline PKD1 gene ( PKD1 mutation). Many clinical cases have been recognized in Japan, but the mutation rate in cats has not been reported. The objective of this study was to determine epidemiological characteristics and clinical feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 22 publications
3
21
1
3
Order By: Relevance
“…Since then, several studies have reported high disease prevalence in mainly Persian and Persian-related cat breeds: 49% in the United Kingdom, 43% in Germany and Australia, 42% in France, 36% in Slovenia, 41% in Italy, and 40% in Japan. 1 -3,7,8,13,26…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several studies have reported high disease prevalence in mainly Persian and Persian-related cat breeds: 49% in the United Kingdom, 43% in Germany and Australia, 42% in France, 36% in Slovenia, 41% in Italy, and 40% in Japan. 1 -3,7,8,13,26…”
Section: Introductionmentioning
confidence: 99%
“…Considering the five Brazilian geopolitical regions and applying a molecular-based screening in a population of 616 cats, this study showed that the prevalence of ADPKD in Persian cats and related breeds was 5.03% and 1.6%, respectively. These results were different from those found in other countries, including the U.S., Australia, UK, France, Italy, Slovenia, Taiwan, Iran and Japan, which showed an estimated 15.7% to 50% of Persian cats and related breeds affected by ADPKD diagnosed by ultrasound exam or genetic testing (Cooper, 2000;Barrs et al, 2001;Beck and Lavelle, 2001;Cannon et al, 2001;Barthez et al, 2003;Kappe et al, 2005;Helps et al, 2007;Domanjko-Petrič et al, 2008;Bonazzi et al, 2009;Wills et al, 2009;Lee et al, 2010;Tavasolian et al, 2018;Noori et al, 2019;Sato et al, 2019).…”
Section: Discussionmentioning
confidence: 58%
“…Based on ultrasonographic and molecular methods, the prevalence of ADPKD among Persian, Persian-related breeds and mixed-breed cats has been shown to be approximately 38% in the United States (Cooper, 2000); 42% to 50% in Australia (Barrs et al, 2001;Beck and Lavelle, 2001), 49.2% in United Kingdom (UK) (Cannon et al, 2001), 40.45% in France (Barthez et al, 2003), 41% in Italy (Bonazzi et al, 2009), 36% in Slovenia (Domanjko-Petrič et al, 2008), 15.7% in Taiwan (Lee et al, 2010), 33.8% to 36.8% in Iran (Tavasolian et al, 2018;Noori et al, 2019), and 46% in Japan (Sato et al, 2019) with no difference between genders ( Barrs et al, 2001; Barthez et al, 2003). In Brazil, however, few studies have determined the prevalence of this disease in specific geographic regions (Ferreira et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This cohort was searched to find novel candidate variants for three diseases and traits; feline autosomal dominant polycystic kidney disease (ADPKD), atrichia, hypotricha. ADPKD is a common inherited autosomal dominant disease affecting about 6% of the world’s cats 49 and is characterized by fluid-filled cysts that form in the bilateral kidneys that often leads to renal failure 50 . Many of the features of feline ADPKD are similar to human ADPKD and recent studies demonstrated the utility of the cat model 14 , 51 .…”
Section: Discussionmentioning
confidence: 99%